A auriculoterapia no tratamento de zumbido no ouvido: uma revisão de escopo - Sousa, Lucas de Lima e (Brasil, 2024)
Tinnitus is characterized by the perception of sounds and/or noises in the absence of stimuli, but its pathophysiological mechanism remains unclear and there are no specific medications for its treatment. In this context, auriculotherapy (AT), also known as auricular acupuncture, is a therapeutic resource used to treat more than 200 health conditions, whether physical or emotional. In Brazil, AT is an Integrative and Complementary Therapy offered by the country's Health System, and it is an accessible, safe, non-invasive and low-cost therapy. The principle of the technique consists of stimulating specific points in the ear, according to the objective of the condition to be treated. In this sense, AT can be an ally in the treatment of health conditions that cause discomfort to the individual, such as acute and chronic pain, from mild to severe intensities, in addition to conditions with a psychological bias, such as stress, anxiety, and depression and, as evidenced by several studies, in the treatment of tinnitus. The objective of this work is to screen the current literature and evaluate, through a scoping review, the effectiveness of auriculotherapy in the treatment of tinnitus. PubMed, Periódicos Capes and Google Schoolar databases were used to search for scientific articles on the topic covered, from 2013 to 2023. Of the 202 studies screened, 7 were included for review and these demonstrated that Auriculotherapy proved to be an effective therapeutic resource in the treatment of tinnitus, regardless of the type of stimulus device and mostly in accordance with the AT points stimulated.